Drosophila suzukii in Michigan vineyards, and the first report of Zaprionus indianus from this region. (7th January 2014) - Van Timmeren, S.; Isaacs, R.
Abstract Drosophila suzukii is a new invasive pest that in recent years has become established in the Great Lakes region of the United States. Understanding the level of infestation in potentially susceptible crops is an important first step for planning appropriate management responses. This study was conducted in 2010–2012 to determine the infestation potential of this pest in native Vitis labrusca, French hybrid and V. vinifera grape cultivars grown in Michigan vineyards. Drosophila suzukii adults were reared out of collected grape samples in all 3 years, comprising a low proportion of all emerged drosophilids in each of the years. This trend was also found in vacuum sampling, conducted in 2011, with the majority of flies collected being non‐D. suzukii drosophilids. Another recently introduced invasive fly species, Zaprionus indianus, was also reared out of grape samples collected in 2012. While the results of this study indicate no immediate threats to commercial grape production from D. suzukii, further research is needed to elucidate possible secondary effects that this species may have on vineyards, such as the introduction of diseases to the fruit.